Qaujimajatuqangit and social problems in modern Inuit society. An elders workshop on angakkuuniq - Oosten, Jarich; Laugrand, Frédéric (Études/Inuit/Studies, 2002)
This paper discusses the main results of a workshop on "Integrating Inuit Qaujimajatuqangit into methods of social control" that was held in Rankin Inlet in July 2000. The workshop was set up from an anthropological perspective to record the views of Inuit elders on social control and angakkuuniq (shamanism). In many respects the results of the workshop confirm current trends and efforts to strengthen the involvement of Inuit communities in the judicial processes, especially with respect to minor offences. Today Inuit traditional knowledge and values are rapidly eroding. Many knowledgeable elders who grew up in the nomadic period and in contact with shamans are now passing away and with them disappears the knowledge of the great traditions of angakkuuniq and related beliefs and practices. Hence there is an urgent need to record knowledge from Inuit elders with due attention to its richness and local variation. Cet article présente les principaux résultats d’un atelier sur "L’intégration des Inuit Qaujimajatuqangit dans le domaine du contrôle social." L’atelier s’est tenu à Rankin Inlet en juillet 2000. Cet atelier a été organisé dans une perspective anthropologique avec l’objectif de recueillir la vision des aînés sur le contrôle social et sur l’angakkuuniq (chamanisme). À bien des égards, les résultats de ces échanges confirment le bien fondé des initiatives contemporaines visant à favoriser autant que possible la participation des Inuit aux différents processus juridiques, et en particulier ceux concernant les délits mineurs. Aujourd’hui, les savoirs traditionnels des Inuit ainsi que certaines de leurs valeurs fondamentales paraissent d’autant plus menacés que les aînés qui ont connu la vie nomade de jadis et vécu au contact des chamanes sont en train de disparaître, emportant avec eux des pans entiers des riches traditions chamaniques. Si la collecte de données auprès des aînés s’avère urgente sur ces thématiques, elle doit s’accompagner d’une prise en compte des richesses régionales et des variations ...